Analisis Perbandingan Anggaran Biaya Operasional dan Anggaran Pendapatan dalam Menilai Kinerja Keuangan pada PT Dunia Barusa Toyota Meulaboh Tahun 2021–2022 - Muliati, Muliati; Annas, Alfian (Regress: Journal of Economics & Management, 2025)
This study examines the comparative relationship between the operating expense budget and the revenue budget in assessing financial performance at PT Dunia Barusa Toyota Meulaboh during the 2021–2022 period. The research addresses whether differences between budgeted and realized figures significantly influence financial performance, as measured by Return on Assets, and which budget component contributes more substantially. A quantitative comparative approach was employed, utilizing primary data obtained through direct interviews with personnel involved in budget preparation. Data were analyzed using multiple linear regression and hypothesis testing through the t-test, processed with the Statistical Package for the Social Sciences at a significance level of 0.05. The findings reveal that both the operating expense budget and the revenue budget demonstrate a strong relationship with Return on Assets and exert a significant partial effect on financial performance. These results affirm that effective budgetary planning and control constitute critical determinants of corporate financial performance.